2007
DOI: 10.1073/pnas.0703442104
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene and Holocene environmental history of the Iguala Valley, Central Balsas Watershed of Mexico

Abstract: The origin of agriculture was a signal development in human affairs and as such has occupied the attention of scholars from the natural and social sciences for well over a century. Historical studies of climate and vegetation are closely associated with crop plant evolution because they can reveal the ecological contexts of plant domestication together with the antiquity and effects of agricultural practices on the environment. In this article, we present paleoecological evidence from three lakes and a swamp l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
108
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 22 publications
(18 reference statements)
1
108
0
2
Order By: Relevance
“…The potential vegetation of the region is tropical deciduous forest, seen today in remnants scattered throughout the region. Vegetational reconstructions indicate that a species-diverse seasonal tropical forest flourished there after the Pleistocene ended and until systematic human disturbance began (27). The native vegetation contains legumes and many other plants that would have been important subsistence resources, such as Pithecolobium dulce, Prosopis spp, Leucaena spp., Spondias spp., palms, Dioscorea spp., and others (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential vegetation of the region is tropical deciduous forest, seen today in remnants scattered throughout the region. Vegetational reconstructions indicate that a species-diverse seasonal tropical forest flourished there after the Pleistocene ended and until systematic human disturbance began (27). The native vegetation contains legumes and many other plants that would have been important subsistence resources, such as Pithecolobium dulce, Prosopis spp, Leucaena spp., Spondias spp., palms, Dioscorea spp., and others (27).…”
mentioning
confidence: 99%
“…Vegetational reconstructions indicate that a species-diverse seasonal tropical forest flourished there after the Pleistocene ended and until systematic human disturbance began (27). The native vegetation contains legumes and many other plants that would have been important subsistence resources, such as Pithecolobium dulce, Prosopis spp, Leucaena spp., Spondias spp., palms, Dioscorea spp., and others (27). Bedrock in the study area is predominantly limestone, although extrusive igneous formations are found in the eastern portion of the area.…”
mentioning
confidence: 99%
“…Combining studies of climate, vegetation, and land-use history with archaeological work, Piperno and her colleagues have developed a picture of human occupation together with the agricultural and environmental history of the region. Their analyses of phytoliths and pollen from the lake cores found the same kinds of environmental shifts as in other regions of the lowland tropics, with a rapid and marked transition to the present warmer, wetter climate taking place at the end of the Ice Age approximately 10,000 years ago (5).…”
Section: Investigating the Cradle Of Maizementioning
confidence: 99%
“…Piperno sampled sediments from the lake edges specifically because she thought that people would have used these fertile areas. Indeed, they found phytoliths from maize and a domesticated species of squash in these areas that are probably at least 8,000 years old (5). Her Inaugural Article (5) focuses on the microfossil evidence from the lakes.…”
Section: Investigating the Cradle Of Maizementioning
confidence: 99%
See 1 more Smart Citation